Color and shape compositions in interior design. - Ergashev Alisher Almaxamadovich (Academia One, 2023)
This article delves into the intricate world of interior design, specifically examining the profound influence of color and shape compositions on the overall aesthetics of a space. Through a comprehensive literature analysis, this study aims to identify key trends and insights, followed by an exploration of various methods employed in creating visually appealing interiors. The results provide valuable insights into the symbiotic relationship between color and shape in design, paving the way for a nuanced discussion on the significance of these elements. The discussion section evaluates the implications of the findings and their relevance in contemporary interior design practices. Finally, the article concludes with practical suggestions for designers seeking to optimize the visual impact of spaces through thoughtful color and shape compositions
Keywords: Interior design; color compositions